Studi Kelayakan dan Kepraktisan Media Pembelajaran Audio Visual Berbasis Animasi pada Materi Bilangan Pecahan Sederhana Siswa Sekolah Dasar - Alfira Khoirunnisa; Masrurotul Mahmudah; Nurul Aisyah (Numerical: Jurnal Matematika dan Pendidikan Matematika, 2026)
This study aims to develop animation-based audiovisual learning media to improve studens’ mathematics learning achievement on simple fraction material. The research employed a research and development (R&D) method using the 4D development model, which consists of the Define, Design, Develop, and Disseminate stages. The subjects of this study were 20 third-grade students of Elementary School 1 Banarjoyo. Date were collected through obsevation, interviews, expert validation, and learning outcome tests (pre-test and post test). The results showed that  the developed learning media achieved a high level of validity, with media expert validation reaching 83% (categorized as feasible) and material expert validation reaching 87% (categorized as highly feasible). The effectiveness test indicated an improvement in students’ learning achievement, as evidenced by the increase in the average score from 63,33 in the pre-test to 75 in the post-test. In addition, learning mastery improved from 45% to 75% after the implementation of the learning media. Based on these finding, it can be concluded that the animation-based audiovisual learning media developed is appropriate to be used as an alternative instructional tool in mathematics learning to enhance students’ understanding of fraction concepts and improve their learning achievement.